Saturated R134a flow boiling inside a 4.3 mm inner diameter microfin tube. (18th August 2017) - Longo, Giovanni A.; Mancin, Simone; Righetti, Giulia; Zilio, Claudio; Doretti, Luca
Abstract : The refrigerant charge minimization in refrigerating and air-conditioning systems represents a challenging issue due to the new environmental national and international regulations. The use of smaller smooth tubes, such as with the outer diameter around 5 mm, is becoming more and more common in many applications. More recently, the microfin tubes have also started to be reduced in size to cope with the continuously increasing demand of new, efficient, and compact heat exchangers for air-conditioning and refrigeration equipment. This work investigates the performance of R134a during saturated flow boiling inside a microfin tube with internal diameter at the fin tip of 4.3 mm. Boiling heat transfer coefficients, frictional pressure drops, and critical vapor qualities were measured at 30°C of saturation temperature, by varying the refrigerant mass velocity between 100 and 800 kg m −2 s −1 and the vapor quality from 0.1 to 0.95 at four different heat fluxes: 15, 30, 60, and 90 kW m −2 . Moreover, the reliability of several models for flow boiling heat transfer and pressure drop estimations was assessed by comparing the experimental results with the calculations.